Assessment of Nano-Indentation Method in Mechanical Characterization of Heterogeneous Nanocomposite Materials Using Experimental and Computational Approaches - Karimzadeh, A; R Koloor, S S; Ayatollahi, M R; Bushroa, A R; Yahya, M Y (Scientific reports, 2019)
This study investigates the capacity of the nano-indentation method in the mechanical characterization of a heterogeneous dental restorative nanocomposite using experimental and computational approaches. In this respect, Filtek Z350 XT was selected as a nano-particle reinforced polymer nanocomposite with a specific range of the particle size (50 nm to 4 µm), within the range of indenter contact area of the nano-indentation experiment. A Sufficient number of nano-indentation tests were performed in various locations of the nanocomposite to extract the hardness and elastic modulus properties. A hybrid computational-experimental approach was developed to examine the extracted properties by linking the internal behaviour and the global response of the nanocomposite. In the computational part, several representative models of the nanocomposite were created in a finite element environment to simulate the mechanism of elastic-plastic deformation of the nanocomposite under Berkovich indenter. Dispersed values of hardness and elastic modulus were obtained through the experiment with 26.8 and 48.5 percent average errors, respectively, in comparison to the nanocomposite properties, respectively. A disordered shape was predicted for plastic deformation of the equilateral indentation mark, representing the interaction of the particles and matrix, which caused the experiment results reflect the local behaviour of the nanocomposite instead of the real material properties.